Penerapan Model Problem Based Learning Dalam Inovasi Pembelajaran IPS di Sekolah Dasar - Farida S (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The current time requires qualified human resources capable of competing globally. Global competition challenging competitive human resources, systematic thinking, logical and consistent and can work together. One model of learning that can be applied to the teaching of Social Sciences is the Model Problem Based Learning. Through the model of Problem Based Learning in the Learning of Social Sciences is one of innovation-based learning and cultural character of the nation. Because, in principle, the model provides an emphasis on the cultivation of norms, values ​​and character of the nation's social culture in learners